(untitled) (Brazilian Geographical Journal, 2019)
The turn of the 21st century presents a range of new factors for understanding global productive structures. Geoeconomics assists geopolitics in the exercise of understanding the strategic dimensions of nation states. Thus, in this article I analyze the recent geoeconomic context of the international relations of the multilateral organizations of Latin America, correlating the recent global productive restructuring emphasizing the general points of overvaluation and subsequent devaluation of commodities in the first two decades of the century.